Structural integrity assessment of shield tunnel crossing of a Railway Bridge using orthogonal experimental design. (August 2020) - Zhao, Baoyun; Wang, Xiaoping; Zhang, Chi; Li, Wangcheng; Abbassi, Rouzbeh; Chen, Kun
Highlights: The construction of tunnel by shield causes the settlement of the bridge. Sensitivity analysis on the influence factors of the settlement of the bridge. By integrating orthogonal test and FLAC 3D, the optimal reinforcement scheme is obtained. Using the means of field monitoring to prove the feasibility of the reinforcement measures. Abstract: This paper focuses on the specific project of shield construction across the existing Wuzhun Railway Bridge between Xuanrendun Station and Dadiwobao Station on Urumqi Metro Line 1. A three-factor and four-level model of the Wuzhun Railway Bridge foundation reinforcement scheme is designed based on the principle of the orthogonal experiment. The calculation of each reinforcement scheme is conducted by using FLAC 3D numerical simulation software. The optimal reinforcement scheme of the Wuzhun Railway Bridge foundation through orthogonal design-direct analysis and variance analysis is obtained. The reinforcement of the Wuzhun Railway Bridge is carried out according to the optimal scheme, and the rationality of the reinforcement scheme is verified by comparing and analyzing the numerical simulation data with the monitored data received from the construction site. The research results serve as a guide in the construction of future tunnel shield crossings for the existing railway, and the developed research methodology provides a reference for similar tunnel crossing projects.